Sosialisasi Penggunaan Media Pembelajaran Berbasis ICT - Janwar Tambunan (Journal on Education, 2023)
In the process of implementing learning, it is the duty of educators to provide an effective learning process. This study aims to determine the development of an ICT (Information Communication and Technology) based learning model in the era of the industrial revolution 4.0. This socialization was carried out at Budi Dharma Sidamanik High School. The purpose of this community service in the form of socialization is to increase the competence of teachers in Indonesia in creating, developing and implementing ICT-based learning media. ICT learning is computer- and multimedia-based learning. This research was conducted to increase teachers' understanding and knowledge of ICT-based learning development procedures. The dissemination of this research is subject teachers at SMA Budi Dharma Sidamanik. With an effective and efficient ICT-based learning model, it can attract and stimulate students' creativity to improve the learning process in schools in the era of the industrial revolution 4.0. The results of this study found that ICT-based learning models can improve quality student ability. The solution to this problem is the implementation of training on making ICT-based learning media using Lectora Inspire. This training activity consists of the following stages: 1) field survey (partners); 2) Coordination with school principals and teachers; 3) Program Outreach; 4) Program Implementation; and 5) Evaluation of activities